2018
DOI: 10.1093/ijnp/pyy083
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Rodent Models of Anhedonia

Abstract: A markedly reduced interest or pleasure in activities previously considered pleasurable is a main symptom in mood disorder and psychosis and is often present in other psychiatric disorders and neurodegenerative diseases. This condition can be labeled as “anhedonia,” although in its most rigorous connotation the term refers to the lost capacity to feel pleasure that is one aspect of the complex phenomenon of processing and responding to reward. The responses to rewarding stimuli are relatively easy to study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 170 publications
(264 reference statements)
6
107
0
Order By: Relevance
“…Similarly, antibiotic treatment reverses both the plasma LPS increase and the depressive-like phenotype caused by chronic mild stress, a well-established murine model of depression (36). In line with such evidence, we observed that the CI EtOH paradigm produced anhedonia that correlates with depressive-like symptoms in rodent models (107,108) and in which the microbiota appears to play a role. This anhedonia may be related to the elevation in brain Kyn because, just as antibiotic treatment prevented the CI EtOH-induced elevation of brain Kyn, it also returned the sucrose preference to control values.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, antibiotic treatment reverses both the plasma LPS increase and the depressive-like phenotype caused by chronic mild stress, a well-established murine model of depression (36). In line with such evidence, we observed that the CI EtOH paradigm produced anhedonia that correlates with depressive-like symptoms in rodent models (107,108) and in which the microbiota appears to play a role. This anhedonia may be related to the elevation in brain Kyn because, just as antibiotic treatment prevented the CI EtOH-induced elevation of brain Kyn, it also returned the sucrose preference to control values.…”
Section: Discussionsupporting
confidence: 84%
“…g Two-way ANOVA, VPA exposure: F 1,24 = 1.75, n.s. ; FBR administration: F 1,24 = 4.97, p = 0.0354; interaction: NAcS play a crucial role in reward processing [37,38] as well as in the modulation of social behavior [39][40][41], and repeated treatments that relieve motivational anhedonia in rat models of depression also restore the dopaminergic response to rewarding stimuli in the NAcS [5,15,31,42]. Thus, we tested whether the social deficits induced by VPA exposure were accompanied by an impaired dopaminergic response to social reward, and whether both deficits were rescued by FBR administration from weaning to young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used multiple behavioral measures to examine the impact of chronic phase shifts on depression and anxiety. Anhedonia (i.e., diminished interest or pleasure in all or most activity most of the day) is a core diagnostic symptom of depression and can be readily modeled in rodents using the sucrose consumption test (Scheggi et al, 2018). Reduced sucrose consumption is taken as a measure of anhedonia; an interpretation validated by the demonstration that the same rats do not exhibit reduced consumption to water (Papp et al, 1991;Matthews et al, 1995).…”
Section: Chronic Jet Lag Increases Anxiety and Depressive-like Behaviorsmentioning
confidence: 99%